Tinjauan Kriminologi Terhadap Tindak Pidana Kasus Judi Gelper di Kota Batam - Jovan Pratama; Abdurrakhman Alhakim (KRTHA BHAYANGKARA, 2022)
Technological developments also have an impact on gambling crimes, one of which is gelper gambling or an electronic game arena located in Batam City. Although many gelper places have been closed by the police, until now there are still some points. The purpose of this study was to examine the regional regulation no. 3 of 2003 regarding the tourism sector of Batam City, Law Number 7 of 1974 regarding guidelines for controlling gambling, and Article 303 of the Criminal Code relating to the criminal act of gambling gelper in Batam City and examines the influencing factors, the impact caused through qualitative analysis description, in order to obtain accurate information in accordance with the gelper gambling phenomenon that occurs in society in Batam City and the laws that apply to players and owners of gelper gambling in Batam City. The method used in this research is the method of normative law (legal research) or doctrinal legal research, namely document studies by researching and reviewing various sources of legal material that have been conceptualized in the form of written regulations such as: court decisions or decisions, legal theories, Perpu, principles and principles of law, and opinions of experts. The results of this study conclude that there are still some unscrupulous managers or entrepreneurs who build gelper tourist attractions near settlements and use them as gambling facilities. This clearly violates the provisions of Regional Regulation No. 3 of 2003 concerning Tourism in Batam City in Article 43 paragraph 1, the editorial of which is not specifically explained regarding the sanctions of the manager and the sanctions of the perpetrators who actively participate in the gambling violation, which makes the Regional Regulation unable to provide legal certainty.